How to measure intersexual dominance? - Seex, Lauren; Saccà, Tommaso; Hemelrijk, Charlotte K. (Frontiers in Ecology and Evolution, 2022)
Intersexual dominance (dominance between the sexes) is often assumed to be binary with species categorised as either male- or female-dominant. Yet in many species, the degree of intersexual dominance falls somewhere in the middle of these two extremes. There are several measures of intersexual dominance, but in empirical studies it is not possible to evaluate which is best because the real degree of intersexual dominance is unknown. This evaluation is possible, however, in the agent-based model, DomWorld because individuals have internal dominance values that drive their agonistic behaviour. In the present study, we examined the accuracy of measures of intersexual dominance in DomWorld by the strength of the correlation between the degree of intersexual dominance based on their internal dominance values and the degree of intersexual dominance based on observations of their competitive interactions (similar to observations in empirical studies). We examined the four measures that have been most commonly used in the literature: the proportion of intersexual conflicts won and initiated, the Female Dominance Index (FDI) and the proportion of female-dominant dyads. The FDI was highly accurate, possibly because it was based on intra- and intersexual fights, both of which influence an individual’s dominance. The proportion of intersexual conflicts initiated was similar in its accuracy to FDI and it was the only measure to be unaffected by missing data. Measures were more accurate when groups were smaller, or the intensity of aggression was higher, but their accuracy did not depend on the degree of sexual dimorphism. To best represent dominance relations between the sexes, we recommend reporting both FDI and the proportion of intersexual conflicts initiated.